DCE-CT Perfusion Parametric Coloured Image Using Steepest Gradient Approach Based on Time Frame - E. Ashoor, Habib (EAI Endorsed Transactions on Energy Web, 2020)
Technological advances in medical imaging modality, counting higher special and temporal resolution, have been utilized to aid radiologist in diagnosing, prognostic and, hence, management of brain tumour. After tracer injection, CT scanning along with pharmacokinetic models are applied to measure several hemodynamic parameters used to describe microvasculature within a targeted region of interest (ROI). These parameters are a choice for diagnostic and prognostic and the likelihood of preferable treatment for brain tumour. The perfusion pixel-wise perfusion map image is a fingerprint of abnormality of ROI within brains that aid radiologist to separate between necrotic and neoplastic of tumour territory and to avoid arterial partial-volume averaging. This work aims to generate pixel-wise perfusion map colour image of brain by using the steepest gradient approach based on the time frame of tracer passage.